PENGEMBANGAN EKONOMI BERBASIS PESANTREN (STUDI KASUS PESANTREN MODERN AL-JUNAIDIYAH BIRU KABUPATEN BONE - Agus, Sherly Afriani; Masse, Rahman Ambo; Putra, Trisno Wardy (I-Economics, 2022)
Pesantren-based economic development is an effort in the economic field where Islamic boarding schools are used as a motor to drive an independent economy by using various efforts such as business units. This study purpose to establish the economic development of the Al-Junaidyah Biru Islamic Boarding School, Bone Regency, by using a qualitative descriptive type of research, namely research that explains a situation to problems in the form of facts that occur. The results of this study, it is known that the Al-Junaidyah Biru Islamic Boarding School in Bone Regency has three Business Units, namely, Workshop, Building Leasing and Santri Mart. The delay in economic development is due to the human resources at the Al-Junaidyah Biru Islamic Boarding School, Bone Regency, which tend to be unfamiliar with the business world. Business Unit management is carried out with profit sharing, so that control does not need to be carried out massively. BUY (Foundation Business Entity) is planned to be legally the legal umbrella for various business units that will be formed later. Until now, new relationships have been built with alumni and the surrounding community to run the business unit. The obstacle experienced by the formation of business units at the Al-Junaidyah Biru Islamic Boarding School, Bone Regency, is the lack of human resources, information obtained from the Head of the Al-Junaidyah Biru Islamic Boarding School Business Unit, Bone Regency.